The Dangerous Points of Dry Type Transmission Tower under Ice Load Based on COMSOL - He, Liuhong (Transactions on Engineering and Technology Research, 2024)
With the continuous and rapid development of the energy industry, the application of transmission poles and towers is more and more widespread. In some areas prone to ice and snow disasters. It is necessary to explore the distribution of hazardous points under snow and ice phenomena. In this paper, a simplified model of dry-type strain tower was established based on COMSOL software, and the gradient analysis of transmission tower and cable icing load was carried out. The results show that the connection of the transmission tower and the transmission cable is most prone to damage, and when the ice thickness reaches more than 60mm, the transmission tower will reach the dangerous critical point. This study provides the damage analysis and optimization of dry type tensile tower after ice.